Penerapan Pembelajaran Kooperatif Tipe Two Stay Two Stray dengan Pendekatan Kontekstual pada Materi Zat Aditif - Rahayu, Rizki Kusumaning; Rachmawati, Rivanna Citraning; Hayat, Muhammad Syaipul; Astuti, Yustina Tri (Universitas PGRI Semarang, 2023)
Two Stay Two Stray is a type of cooperative learning that can support active students by providing opportunities to share results and information with other group members. The background problem of this research is the finding that there is still a lack of activeness among students in their learning and group activities. This study aims to determine the level of student activity during learning, as well as the impact of their learning outcomes. The research was conducted at SMP N 36 Semarang in November 2022, with the subjects being students in class VIII F for the academic year 2022/2023. The research method used was descriptive qualitative, and the data collection techniques used included observation, tests, interviews, and documentation. The results of applying the Two Stay Two Stray cooperative learning type in the class of VIII F at SMP N 36 Semarang showed that students exhibited a 85.93% activity level during learning, and their learning outcome completeness reached 81.25%. Based on these percentages, it can be concluded that the Two Stay Two Stray cooperative learning is effective in increasing student activity during learning, which in turn leads to improved learning outcomes.